Tata Kelola Administrasi Kurikulum dan Perpustakaan : Analisis Kualitas Layanan untuk Mahasiswa di SMK Plus Nahdlatul Ulama Sidoarjo - Maulida Nikmatul Azizah; Kafidin Muzakki (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Education plays a crucial role in shaping competent and competitive human resources. At SMK Plus Nahdlatul Ulama Sidoarjo, the success of education relies not only on a quality curriculum but also on effective administrative management and supporting facilities such as libraries. This study aims to analyze the quality of curriculum administration and library services using a descriptive qualitative approach. Data were collected through observations, interviews, and document analysis. The findings indicate that good governance in curriculum administration and library services significantly impacts student satisfaction. Recommendations are expected to assist further development in the management of the curriculum and library, enabling students to optimally utilize educational resources.